KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKOPEDIA DI TAROGONG KALER - Nur Apipah, Sofa; Yusuf, Ramayani (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2024)
This research aims to discuss the influence of service quality on purchasing decisions at E-Commerce Tokopedia. This research was conducted on consumers who made purchases at E-Commerce Tokopedia. The data collection method in this research uses an associative method for the purpose of finding the influence between two variables. This type of research uses a questionnaire or qualitative research filled in by consumer respondents with a total of 120 respondents. This sample was taken as many as 100 respondents. The analysis technique used is a simple regression analysis test using SPSS tools. With Hypothesis H0 being rejected while H1 is accepted and the results are positive, it can be interpreted that service quality influences purchasing decisions on Tokopedia E-Commerce